Embedded system training based on Arduino to improve software programming knowledge for vocational students - Idris Winarno; Aliridho Barakbah; Dadet Pramadihanto; Wahjoe Tjatur Sesulihatien; Tri Harsono; Bima Sena Bayu Dewantara; Setiawardhana Setiawardhana; Arna Fariza; Iwan Syarif; Tessy Badriyah; Ilham Iskandariansyah; Puspasari Susanti (University of Merdeka Malang, 2022)
Vocational high school students majoring in engineering, who are the successors to technology developers in society, need hard skills to enter the workforce. However, the students of SMK Negeri 2 Bangkalan have not received knowledge about embedded systems. In supporting this need, Master in Applied Informatics and Computer Engineering Program at Politeknik Elektronika Negeri Surabaya held a community service program by holding practice-based training on Arduino Uno-based embedded systems. This program is aimed at vocational high school students so that they can improve their abilities and skills in hardware programming and embedded. The method used in this activity is workshop-based training. The workshop includes a basic explanation of recognizing Arduino and embedded systems, a simple Arduino circuit practicum, and questions and answers between tutors and trainees. The results achieved from this activity are indicated by the results of the training evaluation questionnaire. In general, the training material is considered to be in accordance with the need to add insight, knowledge, skills, and expertise. In addition, the practice-based training on Arduino Uno-based embedded systems has provided benefits for students to use technology in their daily lives.